DeLiDAR: Decoupling LiDARs for pervasive spatial computing - KANATTA GAMAGE RAMESH DARSHANA RATHNAYAKE (Institutional Knowledge at Singapore Management University, 2024)
Unbounded proliferation of LiDAR-equipped pervasive devices generates two challenges: (a) mutual interference among emitters and (b) significantly higher sensing energy overhead. We propose a fundamentally different approach for LiDAR sensing, in indoor spaces, that decouples the sensor’s emitter and receiver components. Our proposed approach, called DeLiDAR, centralizes the emitter functionality in one or more stationary nodes that continually emit pulses; this decoupling allows each mobile LiDAR sensor to be an ultra-low power, pure receiver unit consisting solely of passive multiple photodiodes. We explain how the emitter can utilize VLC-based encoding of its pulses to convey parameter settings that allow a receiver device to infer its own point cloud, without requiring any timing or clock synchronization with the emitter. An initial experimental setup, consisting of a Raspberry Pi and an Arduino-based emitter/2-diode receiver, demonstrates the ability to recover the light pulse’s AoA with a resolution of ±5◦. We also highlight key systems challenges to realize DeLiDAR in practice.